Application Of Two-Stage Game Cross- Efficiency Approach To Primary Health Care In Nigeria - Oduh, Adejoh Friday (2023)
This study aims to analyse the performance of primary health care (PHC) in Nigeria by using two states (Benue and Lagos) as case studies and the game theory-based data envelopment analysis (DEA) technique is introduced. Game theory helps to uncover the dominant (leader) stage of an unobservable two-stage decision making unit (DMU) in the absence of prior knowledge.